Presenting a Model of Digital Transformation Affecting the Quality of Accounting Information in Iran’s Capital Market - Baharipour, Abbas; Hassanpour, Shiva; Mohammad Moosaee, Jaber; Jannat Makan, Hossein (Business, Marketing, and Finance Open, 2025)
This study investigates and proposes a model of digital transformation that affects the quality of accounting information in Iran's capital market. In terms of purpose, this research is categorized as exploratory. From the research philosophy perspective, the study adopts a holistic approach that encompasses both positivism and interpretivism. Moreover, the research follows a mixed-methods strategy, integrating both quantitative and qualitative methodologies. Initially, to collect data and propose a preliminary model, library research and a systematic literature review were conducted. Subsequently, using the fuzzy Delphi method—including a semi-structured questionnaire distributed among 18 experts in the fields of accounting and digital transformation—the key components of the study were identified. Then, to validate the developed model, a researcher-made questionnaire was designed based on the dimensions confirmed in the second phase for quantitative validation. A statistical sample of 384 individuals, including accountants, professionals involved in accounting activities, corporate managers, accounting and finance faculty members, and IT personnel, was selected, and the questionnaire was distributed among them to collect quantitative data. The data were analyzed using quantitative methods and the Smart PLS software, and the final research model was developed. The results revealed that the following are the key components influencing the quality of accounting information: integration of artificial intelligence to reduce errors (5 subcomponents), blockchain for data validation (4 subcomponents), strong internal controls (5 subcomponents), enhanced security of financial data (4 subcomponents), real-time financial reporting (5 subcomponents), cloud-based systems for timeliness (5 subcomponents), artificial intelligence for process acceleration (5 subcomponents), impact of digital platforms on timeliness (3 subcomponents), data visualization tools (5 subcomponents), user-friendly financial reporting platforms (5 subcomponents), and stakeholder-focused data usability (5 subcomponents). The findings align with established theoretical frameworks, including the Technology Acceptance Model, Diffusion of Innovations, and Institutional Theory, highlighting the importance of understanding the opportunities and challenges organizations face amid the complexities of digital transformation.